The Use of PowerPoint-Based Interactive Media to Increase Student Learning Motivation at RA Al Wasliyah - Masfufah (Journal of Indonesian Primary School, 2025)
This study aims to determine the effectiveness of the use of PowerPoint-based interactive media in increasing students' learning motivation at RA Al Wasliyah. The background of this research starts from the low motivation of children to learn which is characterized by a lack of attention, participation, and active involvement in the learning process that is still conventional. This research uses the design of Class Action Research (PTK) which is carried out in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subject of the study was RA Al Wasliyah students who amounted to 20 children, consisting of 10 boys and 10 girls. Data were collected through observation, motivational questionnaires, and documentation, then analyzed with qualitative and quantitative descriptive approaches. The results of the study showed a significant increase in learning motivation after the implementation of PowerPoint-based interactive media. In the initial condition, only 45% of children showed high motivation to learn. After the implementation of the action in cycle I, motivation increased to 70%, and in cycle II it reached 90%. The use of PowerPoint equipped with animations, interesting images, and interactive elements has been proven to attract children's attention, foster curiosity, and encourage their active participation during learning activities. Thus, it can be concluded that PowerPoint-based interactive media is effectively used in learning at RA Al Wasliyah to increase early childhood learning motivation.